Analytical methodologies for the detection of SARS-CoV-2 in wastewater: Protocols and future perspectives - Alygizakis, N.; Markou, A. N.; Rousis, N. I.; Galani, A.; Avgeris, M.; Adamopoulos, P.G.; Scorilas, A.; Lianidou,E.S.; Paraskevis, D; Tsiodras,S.; Tsakris, A.; Dimopoulos, M.A.; et al. (Trends Analyt ChemTrends Analyt ChemTrends Analyt Chem, 2020)
In March 2020 the World Health Organization announced a pandemic outbreak. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the causative pathogen for the coronavirus disease-19 (COVID-19) pandemic. The authorities worldwide use clinical science to identify infected people, but this approach is not able to track all symptomatic and asymptomatic cases due to limited sampling capacity of the testing laboratories. This drawback is eliminated by the Wastewater-Based Epidemiology (WBE) approach. In this review, we summarized the peer-reviewed published literature (available as of 28(th) September 2020), in the field of WBE. The commonly used steps (sampling, storage, concentration, isolation, detection) of the analytical protocols were identified. The potential limitations of each stage of the protocols and good practices were discussed. Finally, new methods for the efficient detection of SARS-CoV-2 were proposed.
Keywords: concentration; COVID-19 pandemic; influent wastewater; isolation; molecular methods detection; RT-qPCR; sampling; symptomatic and asymptomatic; temperature storage; wastewater-based epidemiology